A Personalized Autism Diagnosis CAD System Using a Fusion of Structural MRI and Resting-State Functional MRI Data - Dekhil, Omar; Ali, Mohamed; El-Nakieb, Yaser; Shalaby, Ahmed; Soliman, Ahmed; Switala, Andrew; Mahmoud, Ali; Ghazal, Mohammed; Hajjdiab, Hassan; Casanova, Manuel F.; Elmaghraby, Adel; Keynton, Robert; et al. (Frontiers in Psychiatry, 2021)
Autism spectrum disorder is a neuro-developmental disorder that affects the social abilities of the patients. Yet, the golden standard of autism diagnosis is the autism diagnosis observation schedule (ADOS). In this study we are implementing a computer-aided diagnosis system that utilizes structural MRI (sMRI) and resting state functional MRI (fMRI) to demonstrate that both anatomical abnormalities and functional connectivity abnormalities have high prediction ability of autism. The proposed system studies how the anatomical and functional connectivity metrics provides overall diagnosis of whether the subject is autistic or not and are correlated with ADOS scores. The system provides a personalized report per each subject to show what areas are more affected by autism related impairment. Our system achieved accuracy of 75% when using fMRI data only, 79% when using sMRI data only and 81% when fusing both together. Such a system achieves an important next step towards delineating the neurocircuits responsible for the autism diagnosis and hence may provide better options for physicians in devising personalized treatment plans.